Exploring the impact of titanium dioxide nanoparticles (nTiO2) at varied concentrations in combination with Azospirillum brasilense on wheat growth and physiology - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Salim Manoharadas; Akhtar Hameed; Hasan Riaz; Muhammad Aamir Manzoor; Shamsur Rehman; Muhammad Waheed Riaz; Shakeel Sabir; Awais Munir; Muhammad Irfan Akram; Rashid Iqbal (Journal of King Saud University: Science, 2024)
Background: Nanoparticles (NPs), as a novel source of Nano fertilizers in crop production. Titanium dioxide nanoparticles (nTiO2) also have the potential to improve plant growth, but their effect on the wheat crop is not studied enough. Nothing is known about that how nTiO2 specifically effect on wheat crops especially with soil microbes and how much its dose is effective. Azospirillum brasilense is a promising bio-fertilizer that can be applied in combination with nano-fertilizers to increase crop productivity and can enhance the efficiency of other fertilizers. Methods: The present study was planned to investigate the role of different doses of titanium dioxide nanoparticles (nTiO2) with Azospirillum brasilense on the growth and physiology of wheat, having three replications. Eleven treatments were planned in the field condition (T0 = Control (No A. brasilense and No nTiO2), T1 = nTiO2 @20 mg/L, T2 = nTiO2 @20 mg/L + A. brasilense, T3 = nTiO2 @30 mg/L, T4 = nTiO2 @30 mg/L + A. brasilense, T5 = nTiO2 @40 mg/L, T6 = nTiO2 @40 mg/L + A. brasilense, T7 = nTiO2 @50 mg/L, T8 = nTiO2 @50 mg/L + A. brasilense, T9 = nTiO2 @60 mg/L, T10 = nTiO2 @60 mg/L + A. brasilense) having randomized complete block design (RCBD). Results: Results revealed that the individual application of A. brasilense showed significantly higher results in all treatments, but nTiO2 application shows a positive impact on wheat growth, yield, and physiological parameters when used in a lower concentration. nTiO2 @30 mg/L with A. brasilense gives the highest results as compared to all other treatments with the production of higher antioxidant enzymes, nutrient uptake, higher leaf area index, and photosynthesis. Use of nTiO2 @40 mg/L or with the higher dose negatively affects wheat crops, but with the A. brasilense application its negative effect control up to a certain level. Conclusion: This study highlights the potential advantages of combining A. brasilense with nTiO2, for the growth of wheat crops. While A. brasilense alone consistently produced favorable results, lesser doses of nTiO2 also showed promising results but with the combination of nTiO2 and A. brasilense @ 30 mg/L producing the greatest outcomes. The detrimental effects of excessive nanoscale titanium dioxide on plant growth and development, which may result in stress and physiological abnormalities in the plants, are probably the cause of the decrease in crop output at greater nTiO2 concentrations. However, care should be used while utilizing larger nTiO2 concentrations since they could harm wheat crop growth and yield.